Clean water treatment using the filtration method for residents of Loa Duri Ulu Village, Loa Janan District, Kutai Kartanegara - Faisyal Faisyal; Marlinda Marlinda; Amiril Azizah; Dita Andansari; Mustafa Mustafa; Muh. Taufik (Community Empowerment, 2021)
The problem of clean water in Loa Duri Ulu Village, Loa Janan District, Kutai Kartanegara has been going on for a long time ago. The effort of making a water treatment system through this service activity, gives hope to the residents of Loa Duri Ulu village, Loa Janan sub-district to end the suffering of consuming less decent water for the better. The purpose of this service is to meet the needs of clean water through filtration-based water treatment. With the guidance from this community service team, the residents are expected to be able to make their own water treatment systems for their own needs at home. Through this service activity, it can provide benefits to the community in the form of improving the quality of drinking water, so that public health increases.